Attracting Manufacturers to Radical Design Innovation: A Conceptual Study - Puteri Fadzline, Muhamad Tamyez (Universiti Tenaga Nasional, 2016)
The purpose of this conceptual paper is to explore the potential of radical design innovation among manufacturers in Malaysia. It defines and presents the maturity level that has yet to be pursued among furniture manufacturers in terms of design capability in a manner that shed light on the constructs and sets the stage for future research. This will further determine whether companies have been equipped with the right innovation. This study will emphasize the use of qualitative methodologies to develop a more detailed understanding of radical design innovation from a Malaysian perspective. More specifically, it will examine the meaning, causes of design innovation and how comparatively they apply design innovation with Western companies.